Proposição de método de implantação do FMEA: o caso de uma indústria do setor automotivo - Almeida, Marco Aurélio Pimenta de (2014)
Due to the strong influence of globalization, researchers and entrepreneurs have recognized the need and the importance of developing new approaches in order to increase the competitiveness advantage in new products development. In this increasingly competitive scenario, it is highlighted that the companies have to organize themselves to develop products in an efficient, fast and proper manner in the first time. The Failure Mode and Effects Analysis (FMEA) has to be conducted to determine potential risks and evaluate them in relation to its relevance, probability of occurrence and possibility of detection. These risks have to be minimized by introducing preventive actions, considering that the FMEA is an important tool for defects prevention in products. Therefore, the objective of this study is to present the introduction of a more efficient and effective method to perform the FMEA report, proposing improvement actions to speed up its preparation, thus reducing development time and eliminating deviation of interpretation, because for different cross-functional teams, different interpretations in the index of severity, occurrence and detection have been diagnosed for the same products and / or similar applications. As a result, this work adopted the methodology of action research. Based on this study it was suggested a FMEA standardized by process, where all manufacturing processes existing in the studied organization were identified and mapped. This standardization provided a significant time reduction to perform the FMEA from six to two meetings with the cross-functional team and also allowed quick, efficient and systemic feedback looping, consequently gaining productivity and reliability in the product development process as result.